Evaluation of fault location based on voltage sags profiles: a study on the influence of voltage sags patterns - Mokhlis, Hazlie; Mohamad, H.; Bakar, A.H.A.; Li, H.Y. (Praise Worthy Prize, 2011)
Research and development of fault location techniques for distribution system have been given a great emphasis to enhance reliability and quality of power supply. In a recent work, a comprehensive fault location method based on voltage sag profile has been proposed. In relation with this method, this paper presents a further test to evaluate the method performance by using a non-homogenous and unbalanced distribution network. A focus is given more on the influence of voltage sags patterns to the performance of the method. The test results present the strength and limitation of the method when applied for different fault resistances, loading variation and load models.